Sistemas de monitoreo de tránsito vehicular basados en técnicas de segmentación de imágenes (2010)
Traffic surveillance systems promise to improve traffic safety and alleviate traffic jams, among other things. The continuous increase in processing speed of computers in the last decade has led to an increasing emphasis on research and development of automatic traffic surveillance systems in different countries. However, traffic surveillance systems are still an open research area because they are not in a state of maturity that allows them to operate with complete autonomy in the task of regulating traffic. This article presents a review of automatic traffic surveillance systems based on vehicular image segmentation techniques. We present a classification of these systems according to their purpose and nature, and a classification of the most commonly used techniques in such systems.